(untitled) (Revista de Ciências Agroveterinárias, 2025)
The genus Alternaria consists of widely recognised plant pathogens responsible for several important plant diseases, and may also represent prevalent allergens for animals and humans. This study aimed to screen Alternaria spp. in dogs and cats in the North of Portugal. Fur samples were collected using the Mackenzie technique and were inoculated in SDA and PDA, and microscopic identification was performed using dichotomous keys. A total of 286 (83.9%) dogs and 55 (16.1%) cats were studied; 45.0% (n = 157) of the samples were from shelters, and 54.0% (n = 184) were from veterinary clinics. From the samples taken from the 341 animals, mould isolation was achieved in 303 of them. Alternaria alternata was isolated in 23.75% of studied animals, 22.38% in dogs and 30.91% in cats. Positive samples were analysed according to sex, species, age, origin, and clinical signs. Regarding origin, the lowest prevalence value, 17.8%, was found in the shelter, and the highest, 28.8%, in pet clinics, with these differences being statistically significant (p < 0.000). Young, old, pregnant, or immunocompromised (YOPI) owners are at high risk since there is substantial potential exposure to A. alternata by contact with pets and, therefore, a basis for disease transmission.